SEMANTICS AND SYNTAX OF THE PASSIVE CONSTRUCTION IN HAINAN MIN - 李惠琦(Hui-chi Lee) (Taiwan Journal of Linguistics, 2021)
This paper presents the syntactic and semantic features of passive structures in Hainan Min with a focus on the passive semi-lexical verb in Hainan Min, ioh, lexically denoting the verb 'to take.' We offer definitions and examples for the different meanings in the causative-unaccusative spectrum. The meanings of ioh are tested through these definitions, which revealed that ioh expresses meanings from 'causative' to 'passive.' In addition, this paper also provides data for examining the ioh-passives with reference to there, subject-anaphora, idiom chunks, unaccusative/causative alternation, and subject-oriented adverbs. This paper also compares the ioh-passive with the hoo-passive in Taiwan Southern Min and the gei-passive in Mandarin. The passive structures in the three dialects all follow the passivization cartography. In these dialects, the meanings of the passive verbs occupy several points along the causative-unaccusative spectrum, but different dialects have their specific passive verbs, each with its own range of meanings. The passive structure in Hainan Min has not yet been thoroughly studied. Hence, this paper contributes to filling the gap in the knowledge by providing both semantic and syntactic analyses.